Quality of life, pain, anxiety and depression in patients surgically treated with cancer of rectum - SANTOS,Letácio José Freire (2014)
BACKGROUND: The rectum cancer is associated with high rates of complications and morbidities with great impact on the lives of affected individuals. AIM: To evaluate quality of life, pain, anxiety and depression in patients treated for medium and lower rectum cancer, submitted to surgical intervention. METHODS: A descriptive cross-sectional study. Eighty-eight records of patients with medium and lower rectum cancer, submitted to surgical intervention were selected, and enrolled. Forty-seven patients died within the study period, and the other 41 were studied. Question forms EORTC QLQ-C30 and EORTC QLQ-CR38 were used to assess quality of life. Pain evaluation was carried out using the Visual Analogical Scale, depression and anxiety were assessed through Depression Inventories and Beck's Anxiety, respectively. The correlation between pain intensity, depression and anxiety was carried out, and between these and the EORTC QLQ-C30 General Scale for Health Status and overall quality of life, as well as the EORTC QLQ-CR38 functional and symptom scales. RESULTS: Of the 41 patients of the study, 52% presented pain, depression in 47%, and anxiety in 39%. There was a marking positive correlation between pain intensity and depression. There was a moderate negative correlation between depression and general health status, and overall quality of life as well as pain intensity with the latter. There was a statistically significant negative correlation between future depression perspective and sexual function, and also a strong positive correlation between depression and sexual impairments. A positive correlation between anxiety and gastro-intestinal problems, both statistically significant, was observed. CONCLUSION: Evaluation scales showed detriment on quality life evaluation, besides an elevated incidence of pain, depression, and anxiety; a correlation among these, and factors which influence on the quality of life of post-surgical medium and lower rectum cancer patients was observed.